2019
DOI: 10.1016/j.artmed.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Labeling images with facial emotion and the potential for pediatric healthcare

Abstract: HighlightsAutism spectrum disorder (ASD) affects 750,000 American Children under the age of 10.Emotion classifiers integrated into mobile solutions can be used for screening and therapy.Emotion classifiers do not generalize well to children due to a lack of labeled training data.We propose a method of aggregating emotive video through a mobile game.We demonstrate that several algorithms can automatically label frames from video derived from the game.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 32 publications
0
44
0
1
Order By: Relevance
“…However, most classifiers are biased towards neurotypical adults and can fail to generalise to children with ASD. To address this, Kalantarian et al 36 , 37 presented a framework for semi-automatic label frame extraction to crowdsource labelled emotion data from children. The labels consist of six emotions: disgust, neutral, surprise, scared, angry and happy.…”
Section: Resultsmentioning
confidence: 99%
“…However, most classifiers are biased towards neurotypical adults and can fail to generalise to children with ASD. To address this, Kalantarian et al 36 , 37 presented a framework for semi-automatic label frame extraction to crowdsource labelled emotion data from children. The labels consist of six emotions: disgust, neutral, surprise, scared, angry and happy.…”
Section: Resultsmentioning
confidence: 99%
“…There are several limitations of the present study and fruitful avenues for future work. More structured videos, such as those collected in home smartphone autism interventions [ 15 , 16 , 17 , 18 , 19 ], may yield more consistent video difficulty levels due to the standardization of collected videos. Mobile therapeutics in conjunction with crowdsourcing may be leveraged toward longitudinal outcome tracking of symptoms [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since autism consists of a largely behavioral phenotype, video data are a particularly powerful and rich means of capturing the range of social symptoms a child may exhibit in a fast and virtually cost-free manner. Accurate diagnoses and behavioral classifications have been inferred from categorical ordinal labels extracted by untrained humans from the short video clips [ 5 , 6 , 7 , 8 , 9 , 10 ], which are recorded by digital mobile and wearable interventions during use by the child or administering parent [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Such a process can be scaled through crowdsourcing platforms, which allow distributed workers from around the globe to perform short on-demand tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies used crowdsourcing to develop artificial intelligence projects [53][54][55][56][57]. Four of these studies annotated medical data to train machine learning algorithms [53,[55][56][57]. One study found that a three-phase crowdsourcing challenge contest could be used to develop an artificial intelligence algorithm to segment lung tumors for radiation therapy [54].…”
Section: Synthesizing Evidencementioning
confidence: 99%
“…We also found that crowdsourcing may be useful in the development of artificial intelligence projects. Four studies annotated medical data in order to train machine learning algorithms [53,[55][56][57]. Especially as crowdsourcing solicits input from large numbers of people, the resulting big data may provide a platform for machine learning.…”
Section: Strengths and Limitations Of Studymentioning
confidence: 99%